(untitled) (JS (JURNAL SEKOLAH), 2019)
Abstract: Improved Economic Learning Outcomes Class XII Science 1 Based on Simple Applications Using the Peppermint Learning Model of SMA Negeri 9 Pekanbaru. In this case the researcher applies the "Peppermint Model" individually by maximizing it in small study groups. With the application of the peppermint model, it will contribute greatly to improving learning outcomes. From the results of observation in the first cycle obtained 21.2% of students completeness, while in the second cycle 93.9% of students completeness. Here an increase of 72.7% students completeness. The use of the peppermint model is not only until the second cycle, but can be used continuously to obtain maximum results. Keywords: learning outcomes, economics, application, peppermint Abstrak: Peningkatan Hasil Belajar Ekonomi Kelas XII IPA 1 Berbasis Aplikasi Sederhana Menggunakan Model Pembelajaran Peppermint SMA Negeri 9 Pekanbaru. Dalam hal ini peneliti menerapkan œModel Peppermint secara individu dengan memaksimalkannya dalam kelompok-kelompok belajar kecil. Dengan penerapan model peppermint akan memberikan kontribusi yang besar terutama pada peningkatan hasil belajar. Dari hasil obsevasi pada siklus I diperoleh 21.2% ketuntasan siswa, sedangkan pada siklus II 93.9% ketuntasan siswa. Disini terjadi peningkatan sebesar 72.7% ketuntasan siswa. Penggunaan model peppermint tidak hanya sampai siklus II saja, tetapi bisa digunakan secara kontiniu untuk memperoleh hasil yang maksimal. Kata kunci : hasil belajar, ekonomi, aplikasi, peppermint